2020
DOI: 10.2528/pierc19091604
|View full text |Cite
|
Sign up to set email alerts
|

Time and Frequency Domain Feature Extraction Method of Doppler Radar for Hand Gesture Based Human to Machine Interface

Abstract: In the development of hand gesture based Human to Machine Interface, Doppler response feature extraction method plays an important role in translating hand gesture of certain information. The Doppler response feature extraction method from hand gesture sign was proposed and designed by combining time and frequency domain analysis. The extraction of the Doppler response features at time domain is developed by using cross correlation, and the time domain feature is represented by using peak value of cross correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…CW radars can further be classified as Frequency-Modulated CW (FMCW) radars and single-frequency CW (SFCW) radars. Several studies also denote SFCW radars as Doppler radars [33] since their detection mechanism relies heavily on the Doppler phenomenon. SFCW radar sends a single-tone frequency signal and a shift in the frequency of the received signal occurs when it encounters the hand.…”
Section: Hand-gesture Signal Acquisition Through Radarmentioning
confidence: 99%
See 1 more Smart Citation
“…CW radars can further be classified as Frequency-Modulated CW (FMCW) radars and single-frequency CW (SFCW) radars. Several studies also denote SFCW radars as Doppler radars [33] since their detection mechanism relies heavily on the Doppler phenomenon. SFCW radar sends a single-tone frequency signal and a shift in the frequency of the received signal occurs when it encounters the hand.…”
Section: Hand-gesture Signal Acquisition Through Radarmentioning
confidence: 99%
“…Four gestures were used, with an average accuracy of 94.5%. A study published by [33] presented a features extraction method, followed by cross-correlation and peak detector gesture classification. Another very recent study published by Yu and co-workers [57] reported 96.88 % accuracy for Doppler-radar-based HGR using spectrograms as input to the DCNN network.…”
Section: Hgr Through Sfcw (Doppler) Radarmentioning
confidence: 99%
“…In the past decade, radar based HGR has witnessed a great climax and rapid development. From the type of radar, gesture recognition can be divided into ultra bandwidth pulse radar [1,2,3,4] and continuous wave radar [6,7,15,16,8]. For pulse radar, it mainly uses the original data-driven deep learning method to recognize gestures, and the related feature extraction work is less.…”
Section: Gesture Recognitionmentioning
confidence: 99%
“…This paper mainly summarizes the RF applications based on radar. According to the working mode, the radar can be divided into pulse radar [1,2,3,4] and continuous wave radar [5,6,7,8]. Pulse radar intermittently transmits rectangular pulse periodic signals and receives reflected echo signals in the transmission gap to perceive the environment, but pulse radar has a blind area for short-range detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation